(untitled) (Élisée - Revista de Geografía de la Universidad Estatal de Goiás, 2020)
O objetivo deste trabalho é apresentar as implicações ambientais do desenvolvimento das principais atividades agropecuárias da Microrregião de Porangatu-GO, no período de 2007 a 2016. A Microrregião de Porangatu é uma das dezoito microrregiões do estado de Goiás, composta por dezenove municípios e se localiza no norte do estado. No estudo, foram levantados e analisados dados dos principais produtos agropecuários (gado de corte, soja, milho e arroz) e da perda de cobertura de Cerrado. As análises indicaram que a microrregião se destaca no cenário goiano com a criação de gado de corte, mas com tendência à expansão da produção de soja. No entanto, a expansão dessas atividades se dá sobre áreas de vegetação de Cerrado, resultando na perda da biodiversidade, em uma região que ainda há extensas áreas ainda conservadas deste bioma. Palavras-chave: Agronegócio. Cerrado. Impacto ambiental. Norte goiano. Analysis of the main agricultural activities and their environmental implications in the microregion of Porangatu-Goiás -Brazil, from 2007 to 2016 Abstract: The purpose of this work is to show the environmental implications of the development of the main agricultural activities in the Microregion of Porangatu-GO, from 2007 to 2016. The Microregion of Porangatu is one of the eighteen microregions in the state of Goiás and it is composed of nineteen municipalities and is located in the northern state. In the study, data on the main agricultural products (beef cattle, soy, corn and rice) and loss of Cerrado cover were collected and analyzed. The analyzes indicated that the microregion stands out in the state of Goiás with the creation of beef cattle, but being able to expand soy production. However, the expansion of these activities takes place over areas of Cerrado vegetation, which results in the loss of biodiversity, in a region where there are still extensive areas still conserved in this biome. Keyworks: Agrobusiness. Cerrado. Environmental impact. Northern state of Goiás.